The influence of teachers outreach to parents on students academic success - Adeyeye, G. M.; Dasoo, N. (South African Journal of Higher Education, 2025)
This study examines the crucial impact of teacher-parent communication on students' academic achievement, with a specific focus on the Nigerian environment. Despite the widely acknowledged importance of parental involvement in education, socio-economic, cultural, and technological hurdles exacerbate the difficulties in effective communication, limiting teachers' efforts to engage parents. This study used a quantitative research approach to examine the influence of different communication strategies used by teachers and parents on the academic performance of students in four secondary schools located in Ogbomoso, Oyo State, Nigeria. The regression analysis findings indicate a robust association between successful teacher-parent communication and enhanced kid academic performance, highlighting the crucial importance of regular and high-quality interactions. The study emphasizes the need to use efficient communication tactics in order to improve parental engagement and, as a result, enhance student academic performance. This study enhances our understanding of the intricate nature of teacher-parent relationships and how they impact educational outcomes. It emphasizes the importance of continuously exploring and adapting communication strategies in response to the changing educational environment. This article's structure is as follows: The background section delves into the importance of teacher-parent communication and its influence on students' academic achievement. The Aims and Objectives sections delineate the study's principal objectives and specific targets. The sections on research questions and problem statements outline the fundamental inquiries and contextual obstacles under investigation. The literature review analyzes prior research on teacher-parent communication, including various communication approaches, their effectiveness, and the challenges encountered. The Research Methods section provides a detailed account of the approach utilized in this study. The analysis section thoroughly examines and explains the gathered quantitative data. The Interpretation and Discussion section offers an in-depth examination of the results and their significance for educational practices. The conclusion follows, summarizing the study's contributions.